2015
DOI: 10.2308/bria-51259
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Management Incentives and Audit Committee Communication on Auditor Judgment

Abstract: This study investigates the interplay of management and the audit committee on auditor judgments and evidence documentation. In a 2 × 2 between-subjects experiment, 58 experienced auditors were tasked with evaluating an inventory obsolescence issue when management's incentives to influence the auditor were either higher or lower. The auditors were also either provided or not provided with additional communicated expectations from the audit committee that opposed management's aggressive reporting preference. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…While such interactions are likely to increase as a result of AS16, the audit process may further benefit from increased exchanges that include senior-level auditors who are primarily responsible for executing the audit plan. Overall, the findings from Brown and Popova (2016) highlight how the interrelationships among management, the audit committee, and the auditor are necessary to achieve high-quality financial reporting. Audit firms, companies, and regulators can better address how to enhance the audit committee's oversight role and improve financial reporting quality by recognizing management's role and significant influence on corporate governance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While such interactions are likely to increase as a result of AS16, the audit process may further benefit from increased exchanges that include senior-level auditors who are primarily responsible for executing the audit plan. Overall, the findings from Brown and Popova (2016) highlight how the interrelationships among management, the audit committee, and the auditor are necessary to achieve high-quality financial reporting. Audit firms, companies, and regulators can better address how to enhance the audit committee's oversight role and improve financial reporting quality by recognizing management's role and significant influence on corporate governance.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Brown and Popova (2016) provide important insights into how auditors integrate communicated expectations from the audit committee when performing an audit. In particular, the auditors in our study who were provided with additional communication followed the audit committee's guidance by requiring a more conservative inventory obsolescence estimate and also documented evidence that was more critical of management's expressed reporting preference, but only in conditions in which management was viewed as less credible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have affirmed the vital role of audit committees in supporting external auditor especially when disagreements arise between auditors and their client management on accounting policies, estimates and the appropriate application of accounting standards (Park 2018;Brown & Popova 2015;Ng & Tan 2003;Knapp 1985;Knapp 1987;Stewart & Munro 2007;Brown-Liburd et al, 2016;Goodwin-Stewart & Kent 2006;Salleh & Stewart 2012) Two early prominent empirical studies investigated auditor"s ability to resist management pressure when technical disputes arise conducted by Knapp (1985Knapp ( ) & (1978. Knapp (1985) employed a full-factorial experiment using repeated measures technique and developed an experimental questionnaire of 16 randomly-ordered cases distributed to senior loan officers in the USA and sought their perceptions on factors affecting auditor"s ability to resist management pressure.…”
Section: Communicating About Technical Disputes With the Company Manamentioning
confidence: 99%
“…Their findings totally demonstrated that the compensation payment structure has an effect on information transparency. Brown & Popova (2016) studied the relationship between managers' incentives and audit committee connections and its impact on auditors' decisions. They proved that the more directors' bonuses are, there will be more additional and unconventional relationships of audit committee and it will have greater impact on auditors' decisions.…”
Section: Transparency and Quality Of Financial Informationmentioning
confidence: 99%